Perovskite/Silicon‐Nanowire‐Based Hybrid Heterojunctions for Fast and Broadband Photodetectors. Issue 4 (1st February 2021) - Asuo, Ivy M.; Banerjee, Debika; Pignolet, Alain; Nechache, Riad; Cloutier, Sylvain G.
Abstract : A hybrid photodetector fabricated with a halide perovskite and silicon nanowire (SiNW) heterojunction for broadband detection ranging from near‐ultraviolet to near‐infrared is reported. The device fabrication is conducted by directly coating chemically etched vertical SiNW arrays with perovskite thin films and nanofibers produced from liquid precursors. The optimized perovskite thin film/SiNW heterojunction‐based device under 532 nm illumination exhibits excellent spectral responsivity of 13 A W −1, high specific detectivity reaching 10 13 Jones at 0.3 V external bias, and fast rise/fall times of 22.2/17.6 μs. The device shows very good stability under ambient conditions, even after 30 days of storage. Overall, this simple, all‐solution‐based hybrid photodetector offers great potential for the future integrated optoelectronic devices. Abstract : Fabrication of low‐cost hybrid halide perovskite and silicon nanowire heterojunction photodetectors for broadband detection, exhibiting stable and high spectral response under 532 nm light illumination, is discussed.